Management of hypertensive disorders of pregnancy in the postpartum period - Cairns, A (2017)
This thesis aimed to explore whether self-management techniques, effective in essential hypertension, could be applied to women with hypertensive disorders of pregnancy postpartum (HDP). HDP affect one in ten pregnancies, remain a leading cause of maternal death worldwide and are associated with elevated long-term maternal cardiovascular risk. Hypertension often persists postpartum and complications can occur. During the puerperium, multiple stresses on new mothers and their healthcare professionals can distract from good quality blood pressure (BP) management. Transfer of responsibility, from secondary to primary care, increases scope for uncertainty. The primary objective was to develop and test the feasibility of a novel self-management intervention for postnatal antihypertensive treatment. A systematic literature review (39 studies), local audit (n=20) and regional survey (n=101) were conducted to evaluate existing evidence and clinical practice. A pilot randomised controlled trial compared self-management of postnatal antihypertensive medication with usual care (n=91). Taking patients' views of self-management into account is essential to successful implementation and these were captured through qualitative interviews (n=68). A sub-study to assess markers of vascular risk (n=16) was conducted to further evaluate the relationship between postnatal BP and elevated long-term cardiovascular risk. There is a lack of good quality evidence underpinning hypertension management postpartum and widespread inconsistencies in approaches to care. The pilot trial suggested that expanding the study would be feasible, and that self-management may be more effective than usual care in terms of BP control. Strikingly, the 4-5mmHg reduction in diastolic BP observed with self-management persisted to six months, despite the majority of women being off treatment by this stage, reinforcing the idea that BP control during the puerperium may influence cardiovascular remodelling. However, no differences were demonstrated in markers of cardiovascular risk between sub-study groups. Participants commonly preferred self-management to usual care, and reported feeling more in control through this approach.